Stratigraphy, Geometry, and pattern of Imbricated zones, NW Zagros Fold and Thrust Belt in Iraqi Kurdistan Region (Sulaimani Journal for Pure and Applied Sciences, 2021)
The High Folded and Imbricated zones are the formalized name represent the part of the Tectonic sub-division of Iraq and Kurdistan Region of Iraq (KRI). The study of compressional deformation and Stratigraphy are the keys to identify thrust faults structures and define the sequence of thrusting in High Folded and Imbrication zones as a part of Zagros Fold and Thrust Belts. Through this study, we try to describe the compressional thrust faults and stratigraphical unit description. Thrust faults make repetition of the sequences of Jurassic-Triassic Cretaceous sequence over thrust above Cretaceous sequences. In Iran-Iraq border close to Sirwan valley the large thrust faults (Sirwan-Sazan Thrust faults) identify. The fault system makes Triassic formations over-thrust the Valanginian-Albian Balambo Formations. In Balakayati area serious thrust fault exists, which creates twice repetition of Jurassic-Cretaceous formations forming imbrication thrusting system and fault propagation fold. In Bradost-Korek anticlines the Jurassic-Cretaceous formations over-thrust Cenozoic formations. In Kamosk anticline the thrust faults are in the Cretaceous formations. The dimension and the style of the thrust faults are different but generally, most of the decollement layers of the thrusting are the Early Triassic and Middle-Late Jurassic formations. The collection of all these results constrain geological cross-section in Imbricate Zone and restore to obtain the 7.5 km distance of Shortening due to folding and faulting.
Keywords: Compression stress; Imbricated zone; Thrust faults